The Social Aspects of the Pilgrims from the Islamic East during the Hajj (132 AH - 656 AH) - Majid , Maryam Harith Salman; Mohammed , Saddam Jassim (Journal of Ecohumanism, 2025)
The Islamic Eastern pilgrims arrive in large numbers for the Hajj, and their arrival is often likened to a festive occasion, with people gathering to witness it. This was true whether they were arriving from the East or returning from Makkah after performing the Hajj pilgrimage. Their participation was not limited to joyful occasions; they also took part in moments of sorrow.